Assessing economic wellbeing for development sustainability: a review on a potential pathways for sabah - Siti Hajar Samsu; Nelson Lajuni; Wong Sing Yun; Mohamad I’sa Abd Jalil; Dayangku Aslinah Abd Rahim (Penerbit Universiti Malaysia Sabah, 2024)
Sabah, located on the island of Borneo in Malaysia, has a diverse economy driven by various sectors. Sabah's economy has historically relied heavily on agriculture. The state is renowned for its production of palm oil, cocoa, and other agricultural commodities. Sabah's fertile land and tropical climate make it well-suited for cultivation. Palm oil is a significant export commodity, contributing substantially to the state's economy. Sabah is blessed with rich biodiversity, stunning natural landscapes, and vibrant indigenous cultures, making it a popular tourist destination. The state's attractions include Mount Kinabalu, one of Southeast Asia's highest peaks, pristine diving sites in places like Sipadan Island, and diverse wildlife in conservation areas such as the Kinabatangan River. Tourism plays a crucial role in Sabah's economy, generating revenue, employment opportunities, and foreign exchange earnings.